2016
DOI: 10.1016/j.cosust.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The multiple roles of sustainability indicators in informational governance: between intended use and unanticipated influence

Abstract: To cite this version:Markku Lehtonen, Léa Sébastien, Tom Bauler. The multiple roles of sustainability indicators in informational governance: between intended use and unanticipated influence. Current Opinion in Environmental Sustainability, Elsevier, 2016, 18, pp

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 46 publications
0
69
0
1
Order By: Relevance
“…While such obstacles have to date limited the direct influence of sustainability and wellbeing indicators as inputs into specific policy and decision outcomes-i.e., "instrumental use"-some researchers highlight the possibility of indirect pathways of influence over a longer term through "conceptual use," in other words, by introducing new ideas and reshaping frameworks of thought and mental models [37,39,[41][42][43]. Another key category is "political use," in which indicators serve as "ammunition" to support users' positions-including legitimizing predetermined positions-and persuade others to see problems in a particular way.…”
Section: Beyond-gdp and Sustainability Indicators: Literature On Impamentioning
confidence: 99%
See 2 more Smart Citations
“…While such obstacles have to date limited the direct influence of sustainability and wellbeing indicators as inputs into specific policy and decision outcomes-i.e., "instrumental use"-some researchers highlight the possibility of indirect pathways of influence over a longer term through "conceptual use," in other words, by introducing new ideas and reshaping frameworks of thought and mental models [37,39,[41][42][43]. Another key category is "political use," in which indicators serve as "ammunition" to support users' positions-including legitimizing predetermined positions-and persuade others to see problems in a particular way.…”
Section: Beyond-gdp and Sustainability Indicators: Literature On Impamentioning
confidence: 99%
“…Although difficult to show precisely, indirect impacts may occur over time through "conceptual use" [37,39,[41][42][43], as the GPI initiative introduced new ideas and thought models. One interviewee suggested that the GPI is perhaps "less of a tool to drive precise changes in policy and more of a lens for elected leaders .…”
Section: Conceptual Usementioning
confidence: 99%
See 1 more Smart Citation
“…In their prefaces to sustainability reports, for example, mayors commonly express the wish to promote accountability, yet beyond such socially valued aims, any publication can also be used as 'ammunition' in political debates (Lyytimäki et al 2013). Since 'use' connotes intentionality, some researchers suggest also probing for information 'influence,' noting that use does not imply influence, and influence does not require conscious use (Lehtonen, Sébastien, and Bauler 2016). Table 2 juxtaposes three main uses, influences and outcomes of sustainability reporting with associated stakeholders, acknowledging that this is a simplification of complex matters.…”
Section: A Framework To Study Reporting Practices and Outcomesmentioning
confidence: 99%
“…Indicators must be policy-relevant, reliable, measurable, wide in scope and simple. In practice, however, indicators for sustainable urban development have been selected on the basis of political prioritisation, perceived importance and/or data availability [69][70][71]. Research stresses the importance of involving stakeholders in the process of selecting the evaluation indicators, especially when monitoring progress towards sustainable development [18,59,62,72].…”
Section: Conceptual Background On Sustainability Indicators In the Comentioning
confidence: 99%